Physical Education singularities and contents in Youth and Adult Education (Research, Society and Development, 2022)
The inclusion of the Physical Education subject in the Youth and Adult Education segment provides the student with access to a universe of information and experiences, which contribute to the improvement of their quality of life. The objective of this study is to present, through a literature review, an analysis in relation to the subject of the discipline in this segment as an integration factor. By studying the characteristics of the student as well as the difficulties presented by teachers when working in this segment, this review aims to present significant proposals in order to facilitate the process of minimizing the conflicts existing in this segment, which has as one of its main characteristics, heterogeneity. The need for research aimed at this segment is visible, aimed at contributing to the resolution of obstacles that are present, and that highlight the importance and responsibility of professional training with regard to the commitment to meet the specificities relevant to the segment.